Hubungan Dukungan Suami (Husband Support) dengan Pemberian ASI pada Bayi di Posyandu Desa Sukoanyar, Kecamatan Pakel, Kabupaten Tulungagung - Fahrul Dwi Saputro; Eny Masruroh; Leny Indrawati (Universitas Muhammadiyah Sidaorjo, 2024)
The best nutrition should be obtained only through breastfeeding alone since the first six months of exclusive breastfeeding (Roesli, 2008). According to WHO (2016) data, exclusive breastfeeding coverage worldwide is only about 36% during the 2007-2014 period. Lack of support from the family, surrounding people and especially husbands, can result in decreased success in breastfeeding in infants and may cause infants to be deprived of nutrients that result in decreased immune system. With this research aims to determine the relationship between husband support (husband support) with breastfeeding in infants at integrated service post Sukoanyar Village Pakel District Tulungagung District. The design used in this research is analytic observational with cross sectional research method where the subject of research is only observed once and the measurement is done to the character or variable of the subject at the time of research. The population of this study were all breastfeeding mothers in the integrated service post of Sukoanyar village that had children aged 0-12 months using total sampling technique with a total of 40 respondents. Data collection using questionnaire sheets. Then the data in the analysis with statistical test spearman rho. The results showed that there was a relationship of Husband Support with Breastfeeding in Infants which showed with ρ = 0,000 and α = 0,05 which means value (ρ ≤ 0,05). Based on the results of the research above shows that there is a relationship between husband support (husband support) with Breastfeeding in infants, which is a good husband support resulting in breastfeeding in infants is also very good. So it is important posyandu and the puskesmas also provide counseling not only to the mother but also to the husband about the importance of providing support to the wife about breastfeeding the baby.